Motiv og kontekst - Jørgensen, Jens Lohfert (K&K - Kultur og Klasse, 2017)
This article deals with the properties and functions of the literary motif in relation to the text’s context. One tendency in present-day literary historiography is a growing scepticism towards contextualism. It takes its point of departure in a wish, on the critic’s part, to engage more actively with the text than a focus on its contexts allows. In the first part of the article, I present two concrete instances of this scepticism. In opposition to it, I defend contextualism – in the specific form of a historiographical practice that is able not only to make literary works more comprehensible to us, but also to make them more strange. I discuss Quentin Skinner’s formulation of this idea in the article’s second part. The article’s main thesis is that is by focusing on motifs, rather than themes, that we can verbalize the historical strangeness of literature. In the third part of the article, I discuss the motif’s ability to relate to the text’s context, drawing on the work done of Jesper Gulddal, Ernst Robert Curtius and Erich Auerbach. In the article’s fourth part, I relate my reflections on the relation between motif and context to the motif of bacteria in Danish literature. In three short readings of texts by Johannes V. Jensen, Villy Sørensen and Bjørn Rasmussen, I demonstrate how a focus on the motif at the same time promotes a synchronic perspective on the texts’ relation to their contexts, and a diachronic perspective on their mutual similarities and differences.